Positive Attitude Location Towards Enviroment - Guevara Martínez, Javier; Rodríguez Álvarez, Carolina (Revista de Psicología, 2002)
This research evaluated the behavior of 343 people (chosen at random) from the cities of Apizaco and Huamantla (Tlaxcala State, Mexico). Individuals were chosen from 1600 families and a total population of 8000 citizens. This study is one component of a broader, in-depth research that links all the results of its branches/fields to strengthen them. The aim of this research is to change the way domestic wastes is handled thanks to various influential strategies and social persuasion. The first step to devise solutions to wastes problem is not to create them initially. This becomes true when citizens separate their wastes for re-use in the production process. The study assesses attitudes towards garbage and garbage collection. The pre-test research also uses other instruments/tools concerning populations way of life, which is known as social frame of the population. Secondary research (post-test) will be utilized to evaluate change in behaviors after the use of persuasive strategies. The population already has environment-friendly behavior, however these are very basic (from 0 to 1). We assume that campaigns to protect environment, the position of the government and other groups stressed the importance of environment to the population but not enough to be an end in itself. We do not see major/significative differences according to population and communities characteristics. This research evaluated the behavior of 343 people (chosen at random) from the cities of Apizaco and Huamantla (Tlaxcala State, Mexico). Individuals were chosen from 1600 families and a total population of 8000 citizens. This study is one component of a broader, in-depth research that links all the results of its branches/fields to strengthen them. The aim of this research is to change the way domestic wastes is handled thanks to various influential strategies and social persuasion. The first step to devise solutions to wastes problem is not to create them initially. This becomes true when citizens separate their wastes for re-use in the production process. The study assesses attitudes towards garbage and garbage collection. The pre-test research also uses other instruments/tools concerning populations way of life, which is known as social frame of the population. Secondary research (post-test) will be utilized to evaluate change in behaviors after the use of persuasive strategies. The population already has environment-friendly behavior, however these are very basic (from 0 to 1). We assume that campaigns to protect environment, the position of the government and other groups stressed the importance of environment to the population but not enough to be an end in itself. We do not see major/significative differences according to population and communities characteristics.